Chemotherapy-induced tubulopathy: a case report series - Alamilla-Sanchez, Mario; Diaz Garcia, Juan Daniel; Yanez Salguero, Valeria; Morales Lopez, Fleuvier; Ulloa Galvan, Victor; Velasco Garcia-Lascurain, Francisco; Yama Estrella, Benjamin (Frontiers in Nephrology, 2024)
Acquired tubulopathies are frequently underdiagnosed. They can be characterized by the renal loss of specific electrolytes or organic solutes, suggesting the location of dysfunction. These tubulopathies phenotypically can resemble Bartter or Gitelman syndrome). These syndromes are infrequent, they may present salt loss resembling the effect of thiazides (Gitelman) or loop diuretics (Bartter). They are characterized by potentially severe hypokalemia, associated with metabolic alkalosis, secondary hyperaldosteronism, and often hypomagnesemia. Tubular dysfunction has been described as nephrotoxic effects of platinum-based chemotherapy. We present 4 cases with biochemical signs of tubular dysfunction (Bartter-like/Gitelman-like phenotype) related to chemotherapy.